Expression, purification and crystallization of a dye‐decolourizing peroxidase from Dictyostelium discoideum. Issue 2 (1st February 2014) - Rai, Amrita; Fedorov, Roman; Manstein, Dietmar J.
<x xml:space="preserve">Abstract</x> Dye‐decolourizing peroxidases are haem‐containing peroxidases with broad substrate specificity. Using H2O2 as an electron acceptor, they efficiently decolourize various dyes that are of industrial and environmental relevance, such as anthraquninone‐ and azo‐based dyes. In this study, the dye‐decolourizing peroxidase DdDyP from Dictyostelium discoideum was overexpressed in Escherichia coli strain Rosetta(DE3)pLysS, purified and crystallized using the vapour‐diffusion method. A native crystal diffracted to 1.65 Å resolution and belonged to space group P41212, with unit‐cell parameters a = b = 141.03, c = 95.56 Å, α = β = γ = 90°. The asymmetric unit contains two molecules.